Comparison efficacy and safety of acupuncture and moxibustion therapies in breast cancer-related lymphedema: A systematic review and network meta-analysis. - Yawen Xu; Jiangxuan Yu; Rui Shen; Xueqi Shan; Wenlu Zhou; Junjie Wang (PLoS ONE)
Objective Although several acupuncture and moxibustion therapies have been tested in managing breast cancer-related lymphedema (BCRL), there is little consensus regarding the best options for treating this condition. This systematic review and network meta-analysis compared the efficacy of various acupuncture and/or moxibustion therapies for BCRL. Methods Seven databases and two clinical registration centers were searched from their inception to December 1st, 2023. The Cochrane Collaboration risk-of-bias assessment tool evaluated the quality of included RCTs. A pairwise meta-analysis was performed in STATA 16.0, while a network meta-analysis was performed in R 4.2.2. Results 18 studies were included in this analysis. Our results showed that acupuncture and moxibustion methods had great advantages in improving BCRL of patients with breast cancer. In particular, needle-warming moxibustion (NWM) could be the optimal acupuncture and moxibustion method for improving clinical effectiveness and reducing the degree of swelling of affected limbs. Conclusion Our findings suggest that NWM has great potential in treating BCRL. It may reduce arm circumference, lower swelling levels, and improve clinical effectiveness. Nevertheless, more multi-center, high-quality, and large sample RCTs will be needed in the future.